TLR4/MyD88 expression patterns and novel genetic variants: association with aggressive clinicopathological features in colorectal cancer - Dang, Thai Tra; Pham, Viet Nhat; Tran, Ngoc Dung; Ngo, Thu Hang; Can, Van Mao; Nguyen, Huy Hoang; Nguyen, Thi Xuan; Dang, Thanh Chung (Frontiers in Oncology, 2025)
BackgroundToll-like receptor 4 (TLR4) and myeloid differentiation factor 88 (MyD88) signaling play a critical role in colorectal cancer (CRC) development. Despite extensive research, the relationship between genetic variations and protein expression patterns during adenoma-carcinoma progression remains poorly understood.MethodsWe conducted a cross-sectional study of 176 CRC patients and 131 adenoma patients. Inclusion criteria required histologically confirmed primary colorectal tumors with adequate tissue content (≥30% tumor cells). TLR4 and MyD88 protein expression was evaluated using immunohistochemistry with standardized scoring systems. DNA sequencing identified genetic variants in TLR4 and MyD88 genes. Multivariate analyses assessed associations between protein expression, genetic variants, and clinicopathological features.ResultsTLR4 expression was significantly higher in CRC compared to adenomas (66.5% vs 30.5%, p<0.001), with MyD88 showing widespread expression in both groups (CRC: 97.2%, adenoma: 95.4%). We identified novel variants in TLR4 (9:117713042) and MyD88 (rs138284536), significantly associated with increased CRC risk (OR=8.92, 95% CI: 1.14-69.95, p=0.037 and OR=20.01, 95% CI: 4.72-84.83, p<0.001, respectively). The MyD88 variant correlated with aggressive features including mucinous histology (43.5% vs 22.7%, p=0.036), advanced pT stage (29.6% vs 13.2%, p=0.044), and perineural invasion (61.5% vs 22.1%, p=0.004). Combined TLR4/MyD88 scores ≥5 significantly predicted lymph node metastasis (42.9% vs 28.3%, p=0.046) and high-grade tumor budding (p=0.002).ConclusionsOur study identifies distinct TLR4/MyD88 expression patterns in CRC progression and novel genetic variants associated with aggressive tumor features. These molecular alterations may serve as potential biomarkers for risk stratification and prognostic assessment in CRC patients, while offering promising targets for therapeutic intervention.